“METHODOLOGY FOR ORGANIZING AUDITS OF INSURANCE ORGANIZATIONS” - Maftunakhon Akhmatovna Abduraimova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article discusses the specific features of insurance organizations and delves into issues related to organizing their accounting. Additionally, the process of conducting audits in insurance organizations is examined. The article also covers the procedures for managing the accounting of insurance organizations, conducting analyses, comprehensively evaluating the activities of insurance organizations, and the concept of conducting insurance audits on an international scale. Furthermore, the article provides comparative opinions of scholars on the formulation of financial reports in insurance organizations. It discusses the utilization of analytical practices for the purpose of conducting audits, summarizing audit results, and presenting effective audit findings. In conjunction with this, the article presents important conclusions and practical recommendations regarding the methodology of conducting audits in insurance organizations, thereby elucidating the content and significance of the academic article.